2015
DOI: 10.1136/bcr-2015-213384
|View full text |Cite
|
Sign up to set email alerts
|

Successful removal of uterine leiomyosarcoma tumour thrombus propagating to the right atrium

Abstract: SUMMARYAlthough intravenous leiomyomatosis is widely documented, intravenous extension of leiomyosarcoma into the inferior vena cava (IVC) and subsequently into the right atrium is extremely rare. Less than five such cases have been reported in the literature worldwide. Uterine leiomyosarcoma is an aggressive smooth muscle tumour occurring with an incidence of 1% in all female genital tract cancers and comprises about 3-7% of uterine cancers. It carries a generally poor prognosis with 5-year survival rates ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The largest case series by Perhavec et al showed the most common reasons for technical unresectability to be the involvement of the superior mesenteric vessels, followed by the involvement of bone, portal vein, or hepatic axis (8). When managing an intracardiac tumor thrombus, wide resection is still preferred and intra-operative cardiopulmonary bypass should be considered to facilitate resection and maintain organ perfusion (20)(21)(22) Their rarity poses a great oncologic and surgical challenge, as the bene ts of systemic treatment are unde ned, and surgical management remains controversial. Neoadjuvant therapy can be used to reduce tumor size and improve resectability.…”
Section: Discussionmentioning
confidence: 99%
“…The largest case series by Perhavec et al showed the most common reasons for technical unresectability to be the involvement of the superior mesenteric vessels, followed by the involvement of bone, portal vein, or hepatic axis (8). When managing an intracardiac tumor thrombus, wide resection is still preferred and intra-operative cardiopulmonary bypass should be considered to facilitate resection and maintain organ perfusion (20)(21)(22) Their rarity poses a great oncologic and surgical challenge, as the bene ts of systemic treatment are unde ned, and surgical management remains controversial. Neoadjuvant therapy can be used to reduce tumor size and improve resectability.…”
Section: Discussionmentioning
confidence: 99%